Modular‐structured resonant converter for multilevel converters in micro grids. (17th November 2019) - Reddy P., Vijaya Vardhan; Suryawanshi, H. M.; Nachankar, Pratik P; Talapur, Girish G.; Ballal, Makarand Sudhakar
Summary: In this work, an isolated modular resonant circuit with effective voltage regulation is presented as front‐end for multilevel inverter system to interface renewable sources of energy with micro grid. Inputs of each module of the converter are connected to low‐voltage DC sources. Modular‐structured module outputs may be linked in sequence or parallel to attain the desired DC link capacitor voltage for multilevel inverter. The proposed converter overcomes imbalance in the capacitor voltage of diode‐clamped inverter structure. Interleaved phase shift of 90° is supplied among the gate pulses of all four modules that minimizes the input‐side current ripples. An effective zero voltage switching (ZVS) is achieved over wide load range using duty cycle and frequency‐duty cycle double control method to improve system performance at light load condition. Adopting powder core magnetics and low forward voltage insulated‐gate bipolar transistors (IGBTs) reduces magnetic and conduction loss. A 12‐kW prototype of the designed modular resonant converter was verified by experimentation with a different‐level diode‐clamped inverter structures. Abstract : An isolated modular resonant circuit with effective voltage regulation is proposed as active front end for multilevel inverter system to interface renewable sources of energy with micro grid. The proposed converter overcomes imbalance in the capacitor voltage of diode‐clamped inverter structure. An effective zero voltage switching (ZVS) is achieved over a wide load range using duty cycle and frequency‐duty cycle double control method to improve performance at light load. A 12‐kW prototype is designed and verified by experimentation.